1992
DOI: 10.1128/mcb.12.4.1856
|View full text |Cite
|
Sign up to set email alerts
|

Dioxin-dependent activation of murine Cyp1a-1 gene transcription requires protein kinase C-dependent phosphorylation.

Abstract: Transcriptional activation of the murine Cypla-l (cytochrome P1450) gene by inducers such as 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) (dioxin) requires the aromatic hydrocarbon (Ah) receptor and the interaction of an inducer-receptor complex with one or more of the Ah-responsive elements (AhREs) located about 1 kb upstream from the transcriptional initiation site. We find that treatment of mouse hepatoma Hepa-1 cells with 2-aminopurine, an inhibitor of protein kinase activity, inhibits CYPlAl mRNA induction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
68
1
1

Year Published

1993
1993
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(75 citation statements)
references
References 72 publications
(75 reference statements)
5
68
1
1
Order By: Relevance
“…This effect has been observed in multiple liver cell types [Puga et al, 1992;Enan et al, 1998b;Ashida et al, 2000], but not in all [Gohl et al, 1996]. In other cells, such as LPS-activated B cells, TCDD downregulates AP-1 expression [Suh et al, 2002], suggesting a cell type-dependent effect of AHR ligands on immediate-early protooncogene induction.…”
Section: Ahr Agonists Activate Immediate-early Response Genesmentioning
confidence: 86%
See 1 more Smart Citation
“…This effect has been observed in multiple liver cell types [Puga et al, 1992;Enan et al, 1998b;Ashida et al, 2000], but not in all [Gohl et al, 1996]. In other cells, such as LPS-activated B cells, TCDD downregulates AP-1 expression [Suh et al, 2002], suggesting a cell type-dependent effect of AHR ligands on immediate-early protooncogene induction.…”
Section: Ahr Agonists Activate Immediate-early Response Genesmentioning
confidence: 86%
“…Exposure of multiple rodent cell lines to TCDD results in an essentially immediate increase in protein kinase C levels and activity in cellular membranes [Bombick et al, 1985Madhukar et al, 1988;Carrier et al, 1992]. TCDD specifically activates tyrosine kinases associated with the EGFR [Madhukar et al, 1984[Madhukar et al, , 1988 and induces the association of adaptor proteins such as SHC, GRB2, and SOS with EGFR [Park et al, 1998].…”
Section: Ahr Ligand-dependent Activation Of Signal Transduction Pathwaysmentioning
confidence: 99%
“…Recently, a number of in vivo and in vitro studies have been focused on the effects of protein kinase activation on the specific signal transduction pathways in the control of cyp1A1 gene expression. Notably, protein kinase C-mediated phosphorylation (15,16) appears to be a determinant in the regulation of PAHinducible cyp1A1 gene expression. Our past experiments suggested that PKC-dependent phosphorylation of AhR appears to be required for PAH induction of all of the xenobiotic metabolizing enzymes in the Ah gene battery, not just for cyp1A1 (17).…”
Section: Discussionmentioning
confidence: 99%
“…Carrier et al (15) and Reiners et al (16) have provided evidence that some step in transactivation by the AhR is dependent upon phosphorylation by PKC. Our studies (17) with cultured rat hepatocytes demonstrated that the PKC inhibitors H7 and staurosporine concomitantly inhibited PAH induction of all five genes we tested, including aldh3, cyp1A1, gst1, qor, and ugt1.…”
mentioning
confidence: 99%
“…The activated AhR complex then binds promoter regions of target genes at specific DNA-binding sites (aryl hydrocarbon response elements (AhREs)), thereby modulating gene transcription (Okey et al, 1994;Hankinson, 1995;Porter et al, 2001). A common outcome of AhR activation is the induction of genes such as those encoding the cytochrome P-4501A1, 1A2, and 1B1 monooxygenases (Poland et al, 1974;Whitlock, 1990;Carrier et al, 1992;Larsen et al, 1997). AhR-dependent upregulation of these enzymes results in increased metabolism of some AhR ligands such as PAH and the production of carcinogenic intermediates (Buters et al, 1999;Dertinger et al, 2001).…”
Section: Introductionmentioning
confidence: 99%